(The Effects of size, the amount of coconut fiber and mix cement with mill at producing of Ceiling) - Guring Pohan, H (Warta Industri Hasil Pertanian, 2004)
The research on producing of ceiling was made from grey and white cement mixed with coconut fiber has been conducted. The treatment applied were size and amount of coconut fiber added, cement, white cement, mill and water. the characteristic of product was analysed for is density. moinsture content, water absorption capability, linier and vertical expansion. the result of ceiling product showed that the density was 1.59 grams/cm3, moinsture content 13.6%, water absorption capability 13.06%, vertical expansion 2.74% and linier expansion 0.49% at the treatment of size of coconut fiber were 10-12 cm, and the amount of coconut fiber were 100 grams and mix cement with mill.